Fragile X-associated tremor ataxia syndrome rating scale: Revision and content validity using a mixed method approach - Tosin, Michelle H. S.; Stebbins, Glenn T.; Goetz, Christopher G.; Hagerman, Randi J.; Hessl, David; Zolecki, Melissa A.; Todd, Peter K.; Leehey, Maureen A.; Hall, Deborah A. (Frontiers in Neurology, 2022)
Background: The original Fragile X-associated Tremor Ataxia Syndrome Rating Scale (FXTAS-RS) contained 61 items, some requiring modifications to better meet recommendations for patient-focused rating scale development. Purpose: Provide initial validation of a revised version of the FXTAS-RS for motor signs. Method: We conducted a two-phase mixed-method approach. In Phase 1, revision, we implemented a Delphi technique identifying pertinent domains/subdomains and developing items through expert consensus. In Phase 2, content validation, we conducted cognitive pretesting assessing comprehensibility, comprehensiveness, and relevance of items to FXTAS motor signs. Results: After five rounds of Delphi panel and two rounds of cognitive pretesting, the revised version of the FXTAS-RS was established with 18 items covering five domains and 13 subdomains of motor signs. Cognitive pretesting revealed adequate content validity for the assessment of FXTAS motor signs. Conclusion: The revised FXTAS-RS has been successfully validated for content and it is now ready for large-scale field validation.